Pembentukan dan Pemaknaan Idiom dalam Bahasa Indonesia: Kajian Semantik Kognitif - Beslina Afriani Siagian; Juni Agus Simaremare; Renita Saragih; Enjelina Situmorang (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Bahasa dan Seni, Universitas Negeri Medan, 2024)
Idioms are a representation of the cognition of the speaker community. Idioms are formed from a natural background of knowledge so that they are universal in nature. The main objective of this study is to show the role of cognitive semantic studies in forming Indonesian idioms that represent the experiences of their speakers. This study answers the formulation of problems related to the formation and meaning of idioms. Research data were collected by utilizing various written data as primary data and various other data that can support this study. All of these data were analyzed using various language analysis techniques, such as insert, expand, change form, disappear, replace, and reverse. To ensure the data obtained, triangulation of sources and methods was used. The results of the study showed that through the constructional scheme, frame analysis, and conceptual integration used, it appears that the concepts used by Indonesian speakers in their cognition tend to involve physical (material) or form. Indonesian speakers have very good cognitive abilities in describing meaning through word pairing (idioms).